Building Routines: Learning, Cooperation, and the Dynamics of Incomplete Relational Contracts - Chassang, Sylvain (American Economic Review, 2010)
This paper studies how agents with conflicting interests learn to cooperate when the details of cooperation are not common knowledge. It considers a repeated game in which one player has incomplete information about when and how her partner can provide benefits. Initially, monitoring is imperfect and cooperation requires inefficient punishment. As the players' common history grows, the uninformed player can learn to monitor her partner's actions, which allows players to establish more efficient cooperative routines. Because revealing information is costly, it may be optimal not to reveal all the existing information, and efficient equilibria can be path-dependent. (JEL C73, D82, D83, D86)